The Effects of a Structured Neuromuscular Program on Athletic Performance in Handball: A Controlled Trial with Pre-Post Intervention Analysis - Syed, Anwar Ali S; James, J David Mathew (Physical Education Theory and Methodology, 2025)
Objectives. The study aimed to examine the effects of a six-week neuromuscular training program on agility and explosive power in university-level male handball players using a non-randomized controlled design. Materials and methods. Thirty players (20-24 years) were divided into experimental (n=15) and control (n=15) groups. The experimental group completed five weekly 60-minute neuromuscular sessions, while the control group maintained their regular training regime. Agility (Illinois Agility Test) and explosive power (standing broad jump) were assessed in the pre- and post-intervention phase. Data were analyzed using paired t-tests and ANCOVA (SPSS v22.0, p < 0.05). Results. Following the intervention, the experimental group exhibited statistically significant gains in both agility and explosive power. Agility scores improved from a mean of 16.31 ± 0.92 seconds to 15.81 ± 0.82 seconds (p < 0.001; Cohen’s d = 0.56), while explosive power increased from 2.25 ± 0.15 meters to 2.37 ± 0.12 meters (p < 0.001; d = 0.87). ANCOVA revealed significant group differences after adjusting for pre-test performance (agility: F = 12.36, p = 0.001; explosive power: F = 35.54, p < 0.001). The control group did not show any meaningful changes (p > 0.05). Conclusions. The findings indicate that a six-week neuromuscular training program is an effective method to enhance key performance metrics in handball players, supporting its incorporation into athletic development protocols. Further research should be conducted to investigate the long-term effects and sport-specific transfer.